The effect of water temperature on the human body and the swimming effort - Serafeim, A. (Biology of Exercise, 2014)
Although many research papers have dealt with the influence of environmental temperature on the various Human body functions during exercise in land, a few only informations exist for the equivalent alterations in water temperatures during immersion and swimming. The present preview research paper is referred on this subject. During swimming in the normal water temperature 26° ± 1° C (63), the functions of the human body respond regularly and the performance of swimmers tends to be improved. However, during swimming in cold water critical differences appear in human functions, such as bradycardia, angiospasm, hyperventilation and adaptations of thermoregulatory mechanism which influence the swimming performance and the life itself. Especially in very cold water temperature the disturbances of the cardiovascular system may lead in critical arrhythmia or sudden death. The cold water temperature, however, influences the kinetic and energy behavior related to the reduction of swimmers performance because of its possible influence on the neuromuscular function.In the increased water temperature up to 28° C appears tachycardia, vasodilation and other alternations which aim to better thermoregulation. The swimmers records are possibly equivalent with a tendency to be improved, to the records in normal temperature of championships 26° C and the increased temperature mainly in the speed events (3). Therefore, there is a differentiation on swimmers performances due to water temperature declination from normal. Also, body functions change during water immersion.